White Matter Network Disruption Is Associated With Melancholic Features in Major Depressive Disorder - He, Mengxin; Cheng, Yuqi; Chu, Zhaosong; Wang, Xin; Xu, Jinlei; Lu, Yi; Shen, Zonglin; Xu, Xiufeng (Frontiers in Psychiatry, 2022)
Background: The efficacy and prognosis of major depressive disorder (MDD) are limited by its heterogeneity. MDD with melancholic features is an important subtype of MDD. The present study aimed to reveal the white matter (WM) network changes in melancholic depression. Materials and Methods: Twenty-three first-onset, untreated melancholic MDD, fifty-nine non-melancholic MDD patients and sixty-three health controls underwent diffusion tensor imaging (DTI) scans. WM network analysis based on graph theory and support vector machine (SVM) are used for image data analysis. Results: Compared with HC, small-worldness was reduced and node attributes are abnormal in the right orbital inferior frontal gyrus, left orbital superior frontal gyrus, right caudate nucleus, right orbital superior frontal gyrus, right orbital middle frontal gyrus, left rectus gyrus, and left median cingulate and paracingulate gyrus of MDD patients. Compared with non-melancholic MDD, small-worldness was reduced and node attributes are abnormal in right orbital inferior frontal gyrus, left orbital superior frontal gyrus and right caudate nucleus of melancholic MDD. Correlated with the 7th item score of the HRSD-17 (work and interest), increased node betweenness centrality (aBC) values in right orbital inferior frontal gyrus was positive and decreased aBC in left orbital superior frontal gyrus was negative. SVM analysis results showed that abnormal aBC in right orbital inferior frontal gyrus and left orbital superior frontal gyrus showed the highest accuracy of 81.0%(69/83), the sensitivity of 66.3%, and specificity of (85.2%) for discriminating MDD patients with or without melancholic features. Conclusion: There is a significant difference in WM network changes between MDD patients with and without melancholic features.